If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 6) = 0 Reorder the terms: 3(6 + x) = 0 (6 * 3 + x * 3) = 0 (18 + 3x) = 0 Solving 18 + 3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 3x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 3x = 0 + -18 3x = 0 + -18 Combine like terms: 0 + -18 = -18 3x = -18 Divide each side by '3'. x = -6 Simplifying x = -6
| 5v^2+22v+21=0 | | w^2+10w+16=0 | | 8z+1=9z-2 | | 8x+4=4x-4 | | 7X+15=-6(X-9) | | 0=x(x+3) | | 0=(x+2)(x-7) | | 3y-7=-25 | | -(2s-1)-2=2(4s+0)-2 | | 0=3x^2+14x-5 | | 4(x+4)=7x+22 | | 9z-21=-21+5z | | 3x^2-30x=-4x^2-3x-18 | | 26x^2-30x-4=0 | | q=409-.2p^2 | | (x-23)(55-x)=87 | | 0=x^2-4x-21 | | 10x-28(x-5)=392 | | 4x^2-3x-18=0 | | 0=(2x+1)(x-3) | | 7a-a-5a= | | .75(8x-4)+.5(6x+4)= | | 3X-2X-4= | | 2n^2-143n-390=0 | | .75(8x)= | | -4(66x+166)=11x-4x | | 3(2x+3)=39 | | 3x+7y=36 | | .75(8x-4)= | | (9x-5)(81x^2-90x+25)=0 | | 2*-6-3=y | | 9m-2n-2m+4n= |